Highly Stable, Near‐Unity Efficiency Atomically Flat Semiconductor Nanocrystals of CdSe/ZnS Hetero‐Nanoplatelets Enabled by ZnS‐Shell Hot‐Injection Growth. Issue 8 (30th January 2019) - Altintas, Yemliha; Quliyeva, Ulviyya; Gungor, Kivanc; Erdem, Onur; Kelestemur, Yusuf; Mutlugun, Evren; Kovalenko, Maksym V.; Demir, Hilmi Volkan
Abstract: Colloidal semiconductor nanoplatelets (NPLs) offer important benefits in nanocrystal optoelectronics with their unique excitonic properties. For NPLs, colloidal atomic layer deposition (c‐ALD) provides the ability to produce their core/shell heterostructures. However, as c‐ALD takes place at room temperature, this technique allows for only limited stability and low quantum yield. Here, highly stable, near‐unity efficiency CdSe/ZnS NPLs are shown using hot‐injection (HI) shell growth performed at 573 K, enabling routinely reproducible quantum yields up to 98%. These CdSe/ZnS HI‐shell hetero‐NPLs fully recover their initial photoluminescence (PL) intensity in solution after a heating cycle from 300 to 525 K under inert gas atmosphere, and their solid films exhibit 100% recovery of their initial PL intensity after a heating cycle up to 400 K under ambient atmosphere, by far outperforming the control group of c‐ALD shell‐coated CdSe/ZnS NPLs, which can sustain only 20% of their PL. In optical gain measurements, these core/HI‐shell NPLs exhibit ultralow gain thresholds reaching ≈7 µJ cm −2 . Despite being annealed at 500 K, these ZnS‐HI‐shell NPLs possess low gain thresholds as small as 25 µJ cm −2 . These findings indicate that the proposed 573 K HI‐shell‐grown CdSe/ZnS NPLs hold great promise for extraordinarily high performance in nanocrystal optoelectronics. Abstract : CdSe/ZnS core/hot‐injection (HI) shell nanoplatelets (NPLs) are synthesized with high quantum yields up to 98%, which possess high levels of photo and thermal stability and superior optical gain performance. These core/HI‐shell NPLs exhibit gain thresholds as low as ≈7 µJ cm −2 .